Intermetallic Pd3Pb Nanoplates Enhance Oxygen Reduction Catalysis with Excellent Methanol Tolerance. Issue 3 (1st February 2018) - Wang, Kai; Qin, Yingnan; Lv, Fan; Li, Mingqiang; Liu, Qiao; Lin, Fei; Feng, Jianrui; Yang, Chao; Gao, Peng; Guo, Shaojun
Abstract: Herein, a new class of intermetallic Pd3 Pb square nanoplates (SNP) and nanoplates assemblies is demonstrated with tunable crystalline orientation for boosting oxygen reduction reaction (ORR) activity and stability with excellent methanol tolerance. The Pd3 Pb intermetallic nanostructures show the crystalline‐orientation‐dependent electrocatalytic activity for ORR with (100)‐facet‐dominated Pd3 Pb SNP being the most active. The Pd3 Pb intermetallic SNP exhibits the highest ORR mass activity of 0.78 A mg −1 at 0.9 V versus reversible hydrogen electrode in alkaline electrolyte for the state‐of‐art reported Pd‐based nanocatalysts, 7.1 times higher than that of commercial Pt/C. The unique structure of Pd3 Pb intermetallic SNP makes it highly stable for ORR with almost no activity decrease and no composition and morphology changes after a 5000‐cycle durability test. The Pd3 Pb intermetallic SNP also exhibits much higher methanol tolerance behavior than commercial Pt/C and Pd/C during ORR catalysis. Density functional theory calculations reveal that presence of Pb decreases adsorption strength of methanol on Pd3 Pb intermetallic SNP. The calculated E methanol follows the order of Pd3 Pb (100) < Pd (111) < Pt (111) with (100)‐oriented Pd3 Pb SNP having the lowest methanol adsorption energy, thus boosting methanol tolerance performance. Abstract : Intermetallic Pd3 Pb square nanoplates (SNP) and nanoplates assemblies with tunable crystalline orientation are synthesized by a new procedure. By integrating the thin 2D morphology with tunable crystalline orientation and intermetallic phase, the intermetallic Pd3 Pb SNP with (100) preferred orientation exhibits high mass activity, good stability, and methanol tolerance for oxygen reduction in alkaline media.